A Comparison of Clinical Management and Outcomes Following Either Conventional or Fast Track Perioperative Care in Colorectal Surgery - علوش, علي; قنجراوي, أكثم; عكرمة, سعد (Latakia University Journal -Medical Sciences Series, 2020)
Background: A period of starvation after colorectal anastomosis to permit for resolution of the clinical evidence of ileus has been an unchallenged surgical dogma until recent years. Aim: We intended to determine the safety and feasibility of an early postoperative oral intake protocol in patients experiencing colorectal anastomosis. Materials and Methods: This was a prospective study included 81 patients who underwent colorectal anastomosis at Tishreen University Hospital, Lattakia, Syria during the period between 2019 - 2020. Patients were randomized into two groups. The early feeding group (31 patients) began fluids on the first postoperative day while the regular feeding group (50 patients) was managed in the traditional way ‑ nothing by mouth until the complete resolution of ileus. Results: The two groups were similar in terms of gender, age, and tumor location. The times to first bowel sounds (2.4 ± 0.7 days vs 3.2 ± 0.9 days), first passage of flatus (2.7 ± 0.7 days vs. 3.8 ± 0.72 days) and first passage of stool (4 ± 0.9 days vs. 5.4 ± 0.8 days) were significantly quicker in early feeding group. Hospital stay was also significantly shorter in the early feeding group (5.2 ± 1.2 days vs. 5.9 ± 1.3 days). There was no difference between the groups in terms of nasogastric tube reinsertion, overall complication or anastomotic leakage. Conclusion: Early oral feeding after colorectal surgeries is safe and tolerated by the majority of patients.